Hubungan Tingkat Kecemasan Dengan Tekanan Darah Pada Pasien Pre Operasi Dengan General Anestesi Di RSUD Cilacap - Destiara Putri Nabillah; Amin Susanto; Septian Mixrova Sebayang (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Most people before performing surgery using general anesthetic actionhave emergency surgery. Excessive anxiety reactions are concerned to affect the success of surgery, which can raise blood pressure which improves heart performance while pumping blood throughout the body. Purpose: This investigation aims to find out the relationship between anxiety levels and blood pressure in pre-operative patients under general anesthesia Methods: This study uses a descriptive design of correlation with a cross-sectional approach. Data collection and blood pressure measurement were performed before the respondents entered the operating room by giving them the Amsterdam Preoperative Anxiety and Information Scale questionnaire (APAIS). Samples in thisstudy were taken from 54 respondents using consecutive sampling techniques. Data analysis used is univariate and bivariate analysis using spearman rank tests. Result: The results of correlation statistical test using Spearman rank show that the significance value for systolic blood pressure is 0.007 < 0.05 and for diastolic blood pressure is 0.005 < 0.05. Most of the people who answered experienced systolic blood pressure in stage 1 hypertension, namely 26 people, and diastolic blood pressure in prehypertension, namely 24 people. Conclusion: There is a correlation between the level of anxiety and blood pressure in pre-operative patients under general anesthesia at RSUD Cilacap.